PELATIHAN CUSTOMER SERVICE QUALITY DALAM MENINGKATKAN KINERJA LAYANAN BARISTA (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Abstract: The development of coffee in Indonesia continues to experience significant progress. This is due to the increasing consumption of coffee among the Indonesian people. So that the growth of coffee shops has increased rapidly and experienced intense competition. Intense competition makes coffee shop entrepreneurs compete to offer their best service to attract customers. The absence of five-dimensional customer service excellence is one of the deficiencies that Humble Espresso coffee shop. Therefore, the goal of this training activitiy program is to improve is to increase service quality knowledge and improve barista performance in order to provide fast and professional service to customers. The activity method used is observation, training, and evaluative. The results of the activities achieved were an increase in service quality knowledge and an increase in barista service performance based on the results of the previous questionnaire distribution of 60% and an increase of 80% after training and positive customer perceptions on Google reviews.